White Dwarf Photospheric Abundances in Cataclysmic Variables. IV. Deriving the [N/C] Ratio - Patrick Godon; Edward M. Sion (The Astrophysical Journal, 2023)
We present results from our ongoing far-ultraviolet archival analysis of cataclysmic variable white dwarf (WD) abundances for six more systems: four SU UMa dwarf novae (BW Scl, SW UMa, BC UMa, and VW Hyi) together with the dwarf nova RX And, and the novalike DW UMa. To derive a reliable nitrogen abundance, for the four SU UMa systems (with a WD temperature T _wd ∼ 14,000 to ∼22,000 K), we use the dominant N i (1492 Å) absorption line; for DW UMa (with T _wd possibly as high as 60,000 K), we use the N v (∼1240 Å) doublet; and for RX And (with T _wd = 33,800 K), we use the N iii (1183.0 and 1184.6 Å) absorption lines. We find a [N/C] ratio of the order of 1–100 (in solar units). Oxygen, silicon, phosphorus are mostly underabundant while aluminum is mostly overabundant. We also derive magnesium, sulfur, calcium, and iron for a few systems. VW Hyi has a solar composition secondary implying the suprasolar [N/C] ratio very likely originates in the WD itself, e.g., accretion-driven dredge-up, mixing, and convection bringing material from deeper regions to the WD surface. If the donor star in the other five systems is nonevolved, the WD is the origin for the [N/C] ratio in these systems, either directly as in VW Hyi or due to contamination of the donor and accretion disk by the repetitive explosive CNO burning during the common envelope stage of the nova explosions.